Infliximab Trough Levels at Induction to Predict Treatment Failure During Maintenance. Issue 8 (August 2017) - Liefferinckx, Claire; Minsart, Charlotte; Toubeau, Jean-François; Cremer, Anneline; Amininejad, Leila; Quertinmont, Eric; Devière, Jacques; Gils, Ann; van Gossum, André; Franchimont, Denis
Abstract : Background: Infliximab (IFX) is indicated for the treatment of inflammatory bowel diseases (IBD). Nevertheless, loss of response (LOR) to IFX is reported in up to 10% to 30% of patients within the first year of treatment. Our objective was to evaluate the impact of the pharmacokinetics of IFX at induction on treatment failure. Methods: This is a longitudinal cohort study on 269 patients with IBD treated with IFX in a single center. A total of 2331 blood samples were prospectively collected from 2007 until March 2015 with a retrospective analysis of clinical data. IFX trough levels (TLs) were measured by enzyme-linked immunosorbent assay. Antibodies to IFX were measured by drug-sensitive bridging assay. Results: During follow-up, patients were defined according to treatment outcome. At week 6, median IFX TL in patients requiring a switch to another treatment due to LOR ( LOR switched group ) (2.32 μg/mL [0.12–19.93 μg/mL]) was lower than in patients with long-term response ( long-term responders ) (8.66 μg/mL [0.12–12.09 μg/mL], P = 0.007) and in patients responding to optimization ( LOR optimized group ) (7.28 μg/mL [0.17–14.91 μg/mL], P = 0.021). At week 2, median IFX TL was lower in the LOR switched group (5.7 μg/mL [0.15–12.09 μg/mL]) compared with the long-term responders (11.92 μg/mL [0.14–19.93 μg/mL], P = 0.041) but no significant difference was reached with the LOR optimized group (11.91 μg/mL [0.23–12.09 μg/mL], P = 0.065). In the LOR switched group, median IFX TL at induction (weeks 2 and 6) was significantly lower when patients had been previously exposed to anti–tumor necrosis factor compared with naive patients (0.91 μg/mL [0.12–4.4 μg/mL] versus 6.6 μg/mL [0.15–19.93 μg/mL], P = 0.044). Conclusions: This study suggests that patients who do not respond to any optimization strategy have lower IFX TLs during induction at week 6. IFX TLs measured early on at induction might predict treatment failure to IFX during maintenance. Abstract : Article first published online 11 May 2017.Supplemental Digital Content is Available in the Text.